2017
DOI: 10.1186/s13063-017-2148-4
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers and facilitators to Risk Based Monitoring in academic-led clinical trials: a mixed methods study

Abstract: BackgroundIn November 2016, the ICH published a requirement for sponsors to develop a systematic, prioritised, risk-based approach to monitoring clinical trials. This approach is more commonly known as risk-based monitoring (RBM). However, recent evidence suggests that a ‘gold standard’, validated approach to RBM does not exist and it is unclear how sponsors will introduce RBM into their organisations. A first step needed to inform the implementation of RBM is to explore academic trialists’ readiness and abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
(30 reference statements)
1
17
0
Order By: Relevance
“…There remains a potential benefit in designing triggers based on existing organisational procedures and checks, which are a result of experience and expertise. Hurley et al identified a lack of knowledge on how to define risks and translate them into monitoring activity as one of the main barriers for trialists to implementing RBM [8]; translating current practice into triggers could be a first step.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There remains a potential benefit in designing triggers based on existing organisational procedures and checks, which are a result of experience and expertise. Hurley et al identified a lack of knowledge on how to define risks and translate them into monitoring activity as one of the main barriers for trialists to implementing RBM [8]; translating current practice into triggers could be a first step.…”
Section: Discussionmentioning
confidence: 99%
“…The approach is also encouraged by regulators; the International Conference of Harmonisation (ICH) Good Clinical Practice (GCP) guidance (E6[R2]) advises trialists to “develop a systematic, prioritised, risk-based approach to monitoring clinical trials” [6]. RBM tools support one or both of two components of RBM: an initial risk assessment, which determines the overarching monitoring strategy, and support for ongoing monitoring activities in response to the risks identified [7, 8], including determining the nature and frequency of on-site monitoring visits.…”
Section: Introductionmentioning
confidence: 99%
“…As well as uncertainty about how to develop relevant methods, uncertainty or concern about costs involved is a substantial barrier to adoption of risk-based monitoring. 53 Through our various searches, we identified 24 commercial companies which, we were at least reasonably certain, had a method relevant to our search (data not shown). Scoping review methodology advises that relevant experts in a field are surveyed to help identify other relevant work.…”
Section: /47mentioning
confidence: 99%
“…The increasing number of clinical trials and sites and the growing complexity of study designs make it challenging to detect and identify clinical quality issues timely. Traditional site monitoring strategies, which rely on on-site visits with source data verification (SDV) and on risk-based approaches, are also attempting to mitigate the risk of occurrence of clinical quality issues [3,4]. However, despite extensive audit programs and monitoring activities performed by sponsors, issues related to data integrity, safety, sponsor oversight, protection of primary endpoints and patient consent are recurring audit and inspection findings [5,6].…”
Section: Introductionmentioning
confidence: 99%